2004
DOI: 10.1063/1.1778816
|View full text |Cite
|
Sign up to set email alerts
|

Observation of dendritic flux instabilities in YNi2B2C thin films

Abstract: Magneto-optical imaging and magnetization measurements performed on thin films of the borocarbide superconductor YNi2B2C reveal the occurrence of magnetic flux instabilities upon reducing the applied magnetic field towards the remanent state. In contrast to other low-Tc materials such as Nb and MgB2, where similar instabilities occur in both increasing and decreasing magnetic fields, dendritic flux patterns are observed in YNi2B2C for decreasing fields only. Also in the magnetization measurements, a distinct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 12 publications
9
57
0
Order By: Relevance
“…Magnetisation measurements on MgB 2 thin films [95] soon revealed that flux jumps were ubiquitous below T ≈ 10 K: these jumps were later seen in MO experiments [96] displaying structures as the ones shown in figure 4.1. The phenomenon has later been observed in Nb 3 Sn, YNi 2 B 2 C, patterned Pb, and NbN, in all cases thin films [97,98,99,100]. Magnetisation measurements [101] on plain Pb films also hint strongly at dendritic avalanches below T = 3 K.…”
Section: Dendritic Avalanchesmentioning
confidence: 85%
“…Magnetisation measurements on MgB 2 thin films [95] soon revealed that flux jumps were ubiquitous below T ≈ 10 K: these jumps were later seen in MO experiments [96] displaying structures as the ones shown in figure 4.1. The phenomenon has later been observed in Nb 3 Sn, YNi 2 B 2 C, patterned Pb, and NbN, in all cases thin films [97,98,99,100]. Magnetisation measurements [101] on plain Pb films also hint strongly at dendritic avalanches below T = 3 K.…”
Section: Dendritic Avalanchesmentioning
confidence: 85%
“…[9][10][11][18][19][20][21][22][23][24][25] Such behavior is intimately correlated to thermomagnetic instabilities experienced by the material when heat generated by a sudden displacement of vortices cannot be dissipated, creating thus an increase in the local temperature. This warmer region, in turn, has its pinning capability reduced, being thus likely to host even more vortex motion, reinforcing the process.…”
Section: Resultsmentioning
confidence: 99%
“…These dramatic events occur due to a thermomagnetic instability [1][2][3][4] causing large amounts of flux to rush in from seemingly arbitrary positions along the edge. Magneto-optical imaging (MOI) of the flux penetration in films of many superconducting materials [5][6][7][8][9][10][11][12][13][14][15][16][17] has shown that it is a generic feature of these avalanches that they form nonrepetitive branching structures; see Ref. [18] for a review.…”
mentioning
confidence: 99%